Acoustic description of Croatian accents - Pletikos Olof, Elenmari; Vlašić Duić, Jelena (2007)
This paper presents the descriptive acoustic analysis of Croatian prosodemes, i.e. the four lexical accents and the post-accentual length in the pronunciation of twenty young speakers of Croatian (average age 21.6). The total corpus consisting of 900 tokens has been analysed through listening and after that the auditory unambiguous words (52 % of tokens in the corpus) have been analysed according to acoustic dimensions of duration, intonation and intensity. The results of the acoustic analysis indicate that the mean duration of the stressed vowel in the short-falling accent is 123 ms (SD 28), in the short-rising accent 124 ms (SD 24), in the long-falling 190 ms (SD 33) and in the long-rising 185 ms (SD 33). Post-hoc tests of durational differences show that two long accents are significantly longer than the two short accents (p < .000). Durational differences between rising and falling accents are small and statistically not significant: LF vs. LR (p = .282) ; SF vs. SR (p = .573). In 2/3 of the words the post-accentual phonologically long vowel is perceived as long, and its mean duration is 130 ms (SD 36), that is, 96 % of the total duration of the stressed vowel. Phonologically short post-accentual vowel averagely lasts 95 ms (SD 31), that is, 66 % of the total duration of the stressed vowel. Falling accents have a downward pattern of fundamental frequency in the accented syllable and mostly flat pattern in the post-accentual syllable, while rising accents have a generally flat frequency contour in the accented syllable and a downward contour in the post-accentual syllable. The pitch range (in semitones – ST) within the accented vowel of the long-falling accent is 3.7 ST, of the short-falling accent 2.2 ST, of the long-rising accent 1.4 ST and of the short-rising accent 1.3 ST. The relation between average tone and intensity of the accented and post-accentual vowel indicates that the post-accentual vowel of the falling accents generally has a significantly lower tone and lower intensity than of the rising accents. The pitch level of post-accentual vowel expressed as a ratio of the pitch level of accented vowel in the long-falling accent are -3.8 ST, in the short-falling accent -3.7 ST, in the long-rising accent -1.7 ST and in the short-rising accent -1.2 ST. The intensity level of post-accentual vowel expressed as a ratio of the intensity level of accented vowel (in dB) in the long-falling accents are -8.5 dB, in the short-falling accent -7.6 dB, in the long-rising accent and -7.6 dB and in the short-rising accent -5.5 dB.
Projekt MZOS
Projekt MZOS
ENG